The Economic Impact of Covid-19 on Small and Medium Enterprises in District Swat - Fazal Rahman; Umar Hayat; Muhammad Imad Khan; Rabia Majeed (International Journal of Business and Economic Affairs, 2022)
The present study was undertaken for measuring the economic impact of the COVID-19 on Small and Medium Enterprisesn (SME’s) with reference to District Swat. The Primary data was collected from all of the Tehsils of District Swat using a structured questionnaire. For this purpose a sample of 86 SMEs (20%) from all the manufacturing as well as services sector was selected. The collected data was analyzed using descriptive statistics for selected variables through SPSS. According to the findings, majority of the enterprises faced financial issues for retaining their businesses after COVID-19 lockdown. Majority of the SMEs are owned by moderate level of educated people lacking business education and professionalism. Moreover, during COVID-19 SMEs were negatively affected in term of revenues, expenses and profit. In addition, SMEs were also having debt issues which elevated due to COVID-19 lockdown, resulting in taking loans through traditional mechanism to retain their businesses. Government relief programme was also believed as not sustainable/satisfactory by the significant portion during this period. While humanitarian support from landlords in term of rents waive-off was appreciated. Keeping in view its potential, this sector needs to be boosted through professional trainings on financial, management, leadership and other soft skills training program. Furthermore, relief by government support in term additional relief package and free interest loans are recommended.